Economics of poultry manure as an alternative to chemical fertilizer for agricultural production in Nepal - Subedi, S.; Dhakal, D. (Journal of the Institute of Agriculture and Animal Science, 2018)
This paper explored the potentiality of poultry manure to use as fertilizer in agricultural practices through using descriptive statistics and probit regression model. Result showed that Poultry manure was comparatively more economical than chemical fertilizers regarding same amount of NPK availability for crop production. Sampled households’ age, income, agriculture as main occupation, credit access and membership had significantly determined the level of the application of poultry manure. Farmers perceived that affordable price and soil fertility improvement were the main reasons behind applying it. However, volatization, leaching, improper decomposition, poor market infrastructure and transportation and branding were identified as the major problems associated with its use. Study also revealed that willingness to pay for processed poultry manure was 4 to 7 times higher than what farmers were paying for raw poultry manure. Therefore, either the government or private firms should take initiative in production of processed poultry in Nepal. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, Page: 259-268